(untitled) (Editora Impacto Científico, 2025)
This article introduces the concept of Sustainability from selected authors. Announces the institutional dimension of Sustainability that will be presented, initially, in the light of the International Conference Reports, the Brazilian Constitution and the Statute of Cities, Agenda 21, GEO Brazil 2002. It presents the EPIR method that will be used to evaluate the territory to be studied. When analyzing the word sustainability, many questions are found about its meaning and numerous interpretations and uses are presented. From its history and influence, through the meaning in which it is intended to serve future generations, to its determination regarding the procedures to be adopted, so that the indicated objectives are achieved. Several research works and studies have been or are being prepared in academia, considering their purposes, proposing positions and procedures for their intensification. DOI: https://doi.org/10.56238/edimpacto2025.090-081